Toward safer opioid prescribing: effects of the TOWER intervention on HIV care providers. Issue 4 (3rd April 2022) - Scherer, Maya; Kamler, Alexandra; Weiss, Linda; George, Mary-Catherine; Cedillo, Gabriela; Cárdenas, Luisa; Daniel, Sheaba; DeGarmo, Ellie; Leavell, Yaowaree; Lin, Tiffany; Robinson-Papp, Jessica
ABSTRACT : Rates of opioid use disorder and associated deaths remain alarmingly high. Measures to address the epidemic have included reductions in opioid prescribing, in part guided by the Centers for Disease Control Opioid Prescribing Guideline (CDCG). While reductions in over-prescribing have occurred, these measures have also resulted in decreased access and adverse outcomes for some stable opioid-treated chronic pain patients. The TOWard SafER Opioid Prescribing (TOWER) intervention was designed to support HIV primary care providers in use of the CDCG and in decision-making and patient–provider communication regarding safe opioid prescribing. Eleven HIV primary care providers and 40 of their patients were randomized into intervention and control groups. Transcripts from 21 patient visits were analyzed, focusing on opioid and pain-related communications. Findings from this research indicate greater alignment with the CDCG among visits carried out with providers in the TOWER intervention group. However, control group visits were notably consistent with guideline recommendations in several key areas. Differences observed between the intervention and control group visits demonstrate intervention strengths, as well as areas where additional work needs to be done to ensure prescribing and communication consistent with the CDCG.